2008
DOI: 10.1182/blood-2008-04-150227
|View full text |Cite
|
Sign up to set email alerts
|

Dietary flavonoids inhibit the anticancer effects of the proteasome inhibitor bortezomib

Abstract: Dietary flavonoids have many healthpromoting actions, including anticancer activity via proteasome inhibition. Bortezomib is a dipeptide boronate proteasome inhibitor that has activity in the treatment of multiple myeloma but is not effective in chronic lymphocytic leukemia (CLL). Although CLL cells are sensitive in vitro to bortezomib-induced apoptosis when cultured in medium, the killing activity was blocked when cultured in 50% fresh autologous plasma. IntroductionBortezomib (Velcade) is a first-in-class p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
58
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 47 publications
(81 reference statements)
9
58
3
Order By: Relevance
“…For example, the flavonoid quercetin inhibits bortezomib-induced apoptosis. 40 In contrast to quercetin, we have observed that chemopreventive ITC potentiate the anti-MM effects of bortezomib, and other conventional and novel anti-MM agents. These data provide the framework for future studies of ITC in combination with currently available anti-MM agents: the observed synergy may allow for ITC to be combined with lower doses of other anti-MM agents, thus decreasing the rates and severity of side effects while maintaining potent anti-MM activity.…”
Section: Pies In MMmentioning
confidence: 95%
“…For example, the flavonoid quercetin inhibits bortezomib-induced apoptosis. 40 In contrast to quercetin, we have observed that chemopreventive ITC potentiate the anti-MM effects of bortezomib, and other conventional and novel anti-MM agents. These data provide the framework for future studies of ITC in combination with currently available anti-MM agents: the observed synergy may allow for ITC to be combined with lower doses of other anti-MM agents, thus decreasing the rates and severity of side effects while maintaining potent anti-MM activity.…”
Section: Pies In MMmentioning
confidence: 95%
“…This was speculated to be a result of the single agent use of bortezomib in a heavily pretreated patient population (median lines of prior therapy = four, range 2-11) (Faderl et al, 2006). Moreover, the presence of flavonoids, such as quercetin and myricetin, in the plasma have been attributed to the prevention of CLL cell death and are linked to the chemical reaction between quercetin and the boronic acid group in bortezomib (Liu et al, 2008;Wickremasinghe, 2008). Thus, PIs that do not contain a boron moiety and the partnership of these compounds with additional drugs whose activity complements theirs may be necessary to achieve clinical remission in heavily pretreated CLL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of histone deacetylase inhibitors (HDACis) with Bortezomib within Leukaemia cell lines has demonstrated potential to overcome resistance [41,42]. However, certain natural agents have also been shown to inhibit the actions of Bortezomib, of particular note were the inhibitory actions of the dietary Flavonoid: Quercetin, in B cell lines and primary CLL cells [43]. These potential inhibitory actions highlight the importance of identifying whether natural agents act synergistically with therapeutic agents but also to ensure that they do not inhibit their actions.…”
Section: Apoptotic Inducer Agentsmentioning
confidence: 99%